2015
DOI: 10.1111/liv.12956
|View full text |Cite
|
Sign up to set email alerts
|

Current diagnosis and management of post‐transjugular intrahepatic portosystemic shunt refractory hepatic encephalopathy

Abstract: Transjugular intrahepatic portosystemic shunt has evolved into an important option for management of complications of portal hypertension. The use of polytetrafluoroethylene covered stents enhances shunt patency. Hepatic encephalopathy (HE) remains a significant problem after TIPS placement. The approach to management of patients with refractory hepatic encephalopathy typically requires collaboration between different specialties. Patient selection for TIPS requires careful evaluation of risk factors for HE. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 59 publications
0
36
0
2
Order By: Relevance
“…3 -7 % der Patienten nach TIPS-Implantation sprechen auf eine medikamentöse Therapie der HE jedoch nicht an und sind entsprechend therapierefraktär [707,708]. Interventionelle Verfahren wie die TIPS-Okklusion oder Stentreduktion können in solchen Einzelfällen bei einer akuten HE-Episode hilfreich sein [709,710]. Von 189 Patienten bekamen 12 nach TIPS-Implantation eine HE, die auf eine medikamentöse Therapie nicht ansprach [706].…”
Section: Kommentarunclassified
See 1 more Smart Citation
“…3 -7 % der Patienten nach TIPS-Implantation sprechen auf eine medikamentöse Therapie der HE jedoch nicht an und sind entsprechend therapierefraktär [707,708]. Interventionelle Verfahren wie die TIPS-Okklusion oder Stentreduktion können in solchen Einzelfällen bei einer akuten HE-Episode hilfreich sein [709,710]. Von 189 Patienten bekamen 12 nach TIPS-Implantation eine HE, die auf eine medikamentöse Therapie nicht ansprach [706].…”
Section: Kommentarunclassified
“…Vor Einsatz interventioneller Verfahren sollte eine klare kausale Verbindung zwischen TIPS-Implantation und Auftreten der HE hergestellt werden: Die HE sollte zeitlich nah an dem Eingriff aufgetreten sein, der erzielte portosystemische Gradient ist niedrig und/oder die Leberfunktion verschlechtert sich nach dem Eingriff [710]. Der Vorteil einer Besserung der HE muss gegen das Risiko einer erneuten Varizenblutung oder Aszitesbildung abgewogen werden.…”
Section: Kommentarunclassified
“…A TIPS is useful in the management of the complications of portal hypertension, in particular, gastroesophageal varices, although its insertion precipitates HE [27,28]. A recent study by Routhu et al suggested that several factors (in particular, age, pre-TIPS portal venous pressure, serum creatinine, presence of diabetes mellitus, and etiology of portal hypertension) are significantly associated with the development of overt HE after TIPS [29].…”
Section: Evaluation Associated With the Pathogenesis Of He In Lcmentioning
confidence: 99%
“…41 These methods based on partial or complete occlusion of the shunt have been adopted to control the portosystemic shunt overflow that can occur after a TIPS placement. 42 Although initial attempts at percutaneous shunt occlusion with coils or detachable balloons were successful, 43 these techniques were associated with a high morbidity and mortality 44 related to the recurrence of variceal bleeding or to balloon migration into the right side of the hearth or balloon rupture. Now a days the Amplatzer Vascular Plug (AVP; AGA Medical, Golden Valley, MN, USA) is favored in occluding large-diameter high-flow vessels because of the lack of migration and ease of placement.…”
Section: Techniques Of Tips Reduction-clinical Implications and Litermentioning
confidence: 99%